A CASE–CONTROL STUDY TO ASSESS AND COMPARE THE EFFICACY OF 0.2% CHLORHEXIDINE AND 0.25% SODIUM HYPOCHLORITE MOUTHWASH IN TREATMENT OF CHRONIC GINGIVITIS - Shanker, Kaavya; Suragimath, Girish; Zope, Sameer A; Varma, Siddhartha A; Sr, Ashwinirani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of present study was to compare the efficacy of 0.2% chlorhexidine and 0.25% sodium hypochlorite as a mouthwash in controlling chronic gingivitis. Methods: A total of 80 patients suffering from chronic marginal gingivitis were recruited for the study. Non-surgical periodontal therapy was completed for all the patients to bring the gingival status to healthy levels. The patients were divided into two study groups with 40 patients in each group, Group A patients were asked to use 0.2% chlorhexidine mouthwash, and Group B patients used 0.25% sodium hypochlorite mouthwash as an adjunct to brushing twice daily for 2 weeks. After a period of 2 weeks, the gingival status was recorded using the oral hygiene index simplified (OHIS), plaque index (PI), and modified gingival index (MGI) and compared between the two groups. Results: The mean OHIS score for Group A was 1.38 and for Group B it was 1.05. The mean PI for Group A and B was 3.62 and 2.32, respectively. The mean MGI score for Group A was 1.22 and for Group B was 1.20. Group B showed better results than Group A. Intergroup comparison of OHIS and PI revealed significantly better results in Group B than Group A while MGI did not show any statistical difference on comparison. Conclusion: Nearly 0.25% sodium hypochlorite was more effective than 0.2% chlorhexidine in reducing the gingival inflammation. Thus, 0.25% sodium hypochlorite may represent an efficacious, safe and affordable antimicrobial agent in the prevention and treatment of gingival disease.